Pengaruh Jenis Bakteri PGPR dalam Beberapa Jenis Media Pembawa untuk Meningkatkan Pertumbuhan dan Ketahanan Tanaman Padi Beras Merah Lokal Jatiluwih terhadap Penyakit - NURMALA CZ SITUNGKIR; I MADE SUDANA; I DEWA PUTU SINGARSA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
The Effect of PGPR (Plant Growth Promoring Rhizobacteria) Bacteria in Several Types of Carriers Media to Increase Growth and Resistance of Jatiluwih Local Red Rice Plants Against Disease This study aims to determine the effect of the type of PGPR (Plant Growth Promoting Rhizobacteria) bacteria on the type of carrier media in increasing the growth and resistance of Jatiluwih local red rice rice plants. This research took place from June - December 2019 using the factorial randomized block design (RBD) method.The stages of the research implementation were as follows: 1) Making a carrier media formulation as a biofertilizer. 2) Application of rhizobacteria biofertilizer in red rice rice plants by means of seed treatment. 3) Planting sown brown rice seeds. 4) Maintenance. 5) Observation variable. 6) Data analysis.The results showed that all treatments using a carrier media formula and PGPR rhizobacteria could stimulate the growth and resistance of red rice plants so that the resulting production could increase. Liquid PPG formulation and rhizobacteria PGPR Serratia marcescens is a formula that has better ability than other combination formulas.